Vaginal microbiome-host interactions modeled in a human vagina-on-a-chip - Gautam Mahajan; Erin Doherty; Tania To; Arlene Sutherland; Jennifer Grant; Abidemi Junaid; Aakanksha Gulati; Nina LoGrande; Zohreh Izadifar; Sanjay Sharma Timilsina; Viktor Horváth; Roberto Plebani; et al. (Microbiome, 2022)
Abstract Background A dominance of non-iners Lactobacillus species in the vaginal microbiome is optimal and strongly associated with gynecological and obstetric health, while the presence of diverse obligate or facultative anaerobic bacteria and a paucity in Lactobacillus species, similar to communities found in bacterial vaginosis (BV), is considered non-optimal and associated with adverse health outcomes. Various therapeutic strategies are being explored to modulate the composition of the vaginal microbiome; however, there is no human model that faithfully reproduces the vaginal epithelial microenvironment for preclinical validation of potential therapeutics or testing hypotheses about vaginal epithelium-microbiome interactions. Results Here, we describe an organ-on-a-chip (organ chip) microfluidic culture model of the human vaginal mucosa (vagina chip) that is lined by hormone-sensitive, primary vaginal epithelium interfaced with underlying stromal fibroblasts, which sustains a low physiological oxygen concentration in the epithelial lumen. We show that the Vagina Chip can be used to assess colonization by optimal L. crispatus consortia as well as non-optimal Gardnerella vaginalis-containing consortia, and to measure associated host innate immune responses. Co-culture and growth of the L. crispatus consortia on-chip was accompanied by maintenance of epithelial cell viability, accumulation of D- and L-lactic acid, maintenance of a physiologically relevant low pH, and down regulation of proinflammatory cytokines. In contrast, co-culture of G. vaginalis-containing consortia in the vagina chip resulted in epithelial cell injury, a rise in pH, and upregulation of proinflammatory cytokines. Conclusion This study demonstrates the potential of applying human organ chip technology to create a preclinical model of the human vaginal mucosa that can be used to better understand interactions between the vaginal microbiome and host tissues, as well as to evaluate the safety and efficacy of live biotherapeutics products. Video Abstract